TSL620 : Creative writing / Faculty of Education - UiTM, Faculty of Education (Universiti Teknologi MARA (UiTM), 2020)
Creative Writing (Imaginative writing) is a craft that is developed in the context of everyday experience transformed into imaginative written pieces. Student writers are expected to read, discuss and write/mimic different kinds of poems, fables and/or fairy tales, and short stories. The variety of creative writing pieces will be determined by the students and lecturer as it is best to cater to both their personal idiosyncrasies and preferences for creativity is not rule bound. The creative writing pieces will be an avenue for students to self-explore, self-reflect and self-express. However, not forgetting that the students will graduate as TESL teachers, the language focus should not be deemphasized. Attention will be on the development and refinement of the process of writing like sentence and paragraph construction leading to five to seven (or more) paragraph creative pieces and the composing/writing of poetry, short fiction, drama and etcetera. Lecturers should expect reasonably good writing pieces by the end of the course.